A Case of Wernicke’s Encephalopathy Induced by Pyloric Stenosis - Serkan Özben; Hüsniye Aylin Hakyemez; Hürtan Acar; Feriha Özer (Türk Nöroloji Dergisi, 2009)
Wernicke’s encephalopathy is a neurological syndrome that develops due to thiamine deficiency. Although it has a significantly high mortality rate, it responds well to thiamine treatment, especially in its early stages. Because of its common association with alco- holism and the fact that its clinical triad is seen in only a small portion of patients (10-20%), diagnosis is difficult, especially in cases without a history of alcoholism. Herein we present a patient that drank bleach (sodium carbonate) in an effort to commit suicide and developed pyloric stenosis, which was followed by confusion, ophthalmoparesis, and ataxia